Severe haemolysis and renal failure in a patient with paroxysmal nocturnal haemoglobinuria. Issue 2 (February 1992) - Jackson, G H; Noble, R S; Maung, Z T; Main, J; Smith, S R; Reid, M M
Abstract : Transfusion of about 60 ml of ABO incompatible plasma in 4 units of pooled platelets precipitated severe haemolysis, unmasking the emergence of paroxysmal nocturnal haemoglobinuria (PNH), in a patient with aplastic anaemia. In vitro tests showed that her red cells were lysed by both ABO compatible and incompatible plasma from normal donors. The behaviour of this case and the in vitro results suggest that it might be hazardous to relax the longstanding recommendation on transfusing patients with PNH by restricting the washing of blood components to those containing ABO incompatible plasma.